PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH DITJEN PERBENDAHARAAN PROVINSI MALUKU UTARA DI TERNATE - Nurlaila Nurlaila; Zulaiha Husen (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2017)
This study aims to determine the influence of organizational culture and work motivation partially or simultaneously. The population in this study is all employees at the Regional Office of the Directorate General of Treasury of Maluku Utara Province in Ternate which amounts to 36 people This study is a population study. Data collection techniques used were to spread questionnaires, interviews and observations. Data analysis in this research is using (multiple regression analysis). The results of this study indicate that the organizational culture variable (X1), and work motivation (X2) have a positive and significant effect on the performance of the employees at the Regional Office of the Directorate General of Treasury of North Moluccas Province in Ternate either partially or simultaneously meaning that Ha is accepted and H0 is rejected by So the hypothesis proposed can be verified so that the hypothesis is accepted.